2017
DOI: 10.4049/jimmunol.1601850
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Clustering Can Identify B Cell Clones with High Confidence in Ig Repertoire Sequencing Data

Abstract: Adaptive immunity is driven by the expansion, somatic hypermutation, and selection of B cell clones. Each clone is the progeny of a single B cell responding to antigen, with diversified Ig receptors. These receptors can now be profiled at large-scale by next-generation sequencing. Such data provide a window into the micro-evolutionary dynamics that drive successful immune responses and the dysregulation that occurs with aging or disease. Clonal relationships are not directly measured, but must be computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
221
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(225 citation statements)
references
References 57 publications
2
221
2
Order By: Relevance
“…By definition, clones cannot span different individuals. To estimate specificity, we combine data from multiple individuals, use our proposed method to identify clonal relationships, and then count the frequency of clones that are (incorrectly) inferred to be shared across individuals (Gupta et al, 2017). We use the procedure proposed in (Nouri and Kleinstein, 2018a).…”
Section: The Stress-based Methods Improves the Sensitivity Specificitmentioning
confidence: 99%
See 1 more Smart Citation
“…By definition, clones cannot span different individuals. To estimate specificity, we combine data from multiple individuals, use our proposed method to identify clonal relationships, and then count the frequency of clones that are (incorrectly) inferred to be shared across individuals (Gupta et al, 2017). We use the procedure proposed in (Nouri and Kleinstein, 2018a).…”
Section: The Stress-based Methods Improves the Sensitivity Specificitmentioning
confidence: 99%
“…However, clonal relationships are not directly measured, but they must be computationally inferred. To this end several computational methods have been proposed to identify B cell clones from high-throughput AIRRseq data (Glanville et al, 2011;Kepler, 2013;Ralph and Matsen IV, 2016;Gupta et al, 2017;Nouri and Kleinstein, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Since hypermutation levels will always confound this analysis it is impossible to get 100% specificity and sensitivity in the clonal allocation, but it is easier to split an incorrectly clustered clone upon closer inspection than it is to know about potential missing sequences. A recent paper concluded that single linkage hierarchical clustering with Hamming distance has high performance, with specificity, sensitivity, and positive predictive value all over 99% in their test data 97. More complex clustering algorithms can be employed, such as multi‐hidden Markov models98 which can give different results to hierarchical clustering methods.…”
Section: Clonality Analysismentioning
confidence: 99%
“…A recent paper concluded that single linkage hierarchical clustering with Hamming distance has high performance, with specificity, sensitivity, and positive predictive value all over 99% in their test data. 97 More complex clustering algorithms can be employed, such as multi-hidden Markov models 98 which can give different results to hierarchical clustering methods. Therefore, it is important to check the clustering methods employed if one wants to compare results from different studies.…”
Section: Disseminationmentioning
confidence: 99%
“…Somatic hypermutation may cause uncertainty as to germline gene assignment, and insertion/deletion mutations (indels) may change CDR3 length. However, the assumption of a fixed cutoff, even a per-repertoire fixed cutoff, 155 seems the most problematic.…”
Section: | Clonal Family Inferencementioning
confidence: 99%